The Use of a Locking Plate for the Treatment of Femoral Diaphyseal Fracture in Giant Anteaters (Myrmecophaga tridactyla) - Barssalho, Michelly Amanda; Barranco, Guilherme Henrique Fernandes [UNESP]; Padula, Karina; Almeida, Diego Alaska; de Oliveira, Gracila Heitor; Vilella, Maria Stella Fernandes; Fernandez, Stephanie; de Andrade Cruvinel, Tatiana Morosini; Rossetto, Victor José Vieira (Universidade Federal do Rio Grande do Sul, 2021)
Background: The giant anteater is considered a species vulnerable to trauma due to being slow and, therefore, vulnerable to long bone fractures, such as femoral fracture. Locking plates have the potential to restore and maintain fractured bone stability, as well as reduce damage to the vascular supply. This study aims at reporting cases of two giant anteaters subjected to femoral osteosynthesis using locking plates. Cases: Two giant anteaters presenting non-weight bearing lameness on the right pelvic limbs were evaluated, diagnosed with femoral fracture of unknown etiology and submitted to osteosynthesis. A clinical evaluation was performed under chemical restraint for the adult animal and physical restraint for the young one. Crepitation and swelling in the right femur topography led to a radiographic examination, which showed a complete and transverse diaphyseal fracture of the right femur in both cases. The first one was an adult male and was subjected to osteosynthesis of the right femur using a locking plate. Once anesthetized, the animal was placed in left lateral recumbency, and the right pelvic limb was clipped and sterilized. A craniolateral incision was made to expose the femoral diaphysis. A large amount of fibrous-looking tissue was found and removed. Subsequently, the fracture was reduced and the locking plate system was positioned on the craniolateral side of the femur. An osteotomy of the femoral trochanteric crest was required to position the implant. The overlying fascia lata was closed using monofilament suture in a simple continuous pattern. The closure of the subcutaneous tissue and skin was performed using a Cushing pattern and simple interrupted pattern, respectively. Immediate postoperative radiographic examinations showed fracture reduction and bone axis alignment, with a properly positioned implant. The surgical wound was cleaned daily with 0.5% aqueous chlorhexidine solution. Seven days after surgery, the animal had a partial dehiscence at the suture site, with bone and plate exposure. Wound healing by second intention was initiated. At 127 days after surgery, a radiographic examination showed periosteal bone proliferation in the middle third of the right femur and that the bone implants were well-positioned. The second case was of a young 3.68 kg female anteater. The surgery was performed as described for the adult one, but there was no fibrosis at the fracture site and the osteotomy of the femoral trochanteric crest was not required. Closure of the fascia lata, subcutaneous tissue, and skin was performed as in Case 1. An immediate postoperative radiographic examination showed fracture reduction, bone axis alignment, and a properly positioned implant. The surgical wound was cleaned daily with 0.5% aqueous chlorhexidine solution. On the day of the surgery, the animal could already bear weight on its right pelvic limb, presenting discrete lameness with gradual improvement. Twenty-three days after surgery, a radiographic examination showed moderate periosteal bone proliferation in the middle third of the right femur. The bone implant was still well-positioned and bone healing was achieved around the 40th post-operative day. Discussion: The cases are very similar, but the younger anteater's femoral trochanteric crest didn't prevent positioning the plate. The fibrosis observed on the adult specimen is indicative of a chronic fracture, which may explain, in conjunction with the post-surgical complications, the longer time required for bone healing in the adult animal. Even so, both animals recovered fully and it's safe to deduce that the locking plate is an adequate option for internal fixation in transverse diaphyseal femoral fractures in both adult and young giant anteaters.
Keywords: Animals; Fracture fixation; Internal; Mammals; Wild